Stability analysis in quality protein maize (Zea mays) by Eberhart and Russell model, and GGE biplots - SWAPNIL; RASHMI, KUMARI; SAHAY, SANJAY; MANDAL, S S; SINHA, SWETA; SINGH, BIRENDER; SINGH, DIGVIJAY; PARWEEN, RABIYA; IMAM, ZAFAR (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during winter (rabi) 2019–20, 2020–21 and rainy (kharif) season of 2021 at Bihar Agricultural University, Sabour, Bihar to study the stability in Quality Protein Maize (QPM) (Zea mays L.). A total of 50 QPM inbred lines were screened during rabi 2019–20 out of which 14 inbred lines and 3 testers were selected as the promising genotypes. These lines and testers were hybridized to generate 42 crosses utilizing the line × tester fashion. The 61 genotypes (42 crossings, 14 lines, 3 testers and 2 checks) were assessed in three distinct environments viz. early kharif (sown on May 15), E1; kharif (sown on June 30), E2; and late kharif (sown on August 15), E3 using a randomized complete block design (RCBD) with three replications. The data were recorded for 18 morphological and biochemical traits to draw conclusions on stability analysis using Eberhart and Russell model, and GGE biplots. The Eberhart and Russell model’s estimations of stability study for grain yield showed that 7 hybrids, viz. L5 × T3, L6 × T2, L6 × T3, L7 × T1, L13 × T3, L14 × T1 and L14 × T2 were stable in a range of environmental circumstances. Similarly, using GGE biplots three hybrids (L5 × T3, L6 × T3 and L13 × T3) were found as the stable ones and the late kharif environment ranked the best for identifying the high-yielding genotypes.